Friction stir processing of 3D-printed metal composites - Lim, Dalton Jun Jie (2016)
The use of metal matrix composites has gain increasing interest over the decades due to in superior properties over pure metal components. Combining metallic and non-metallic material to form a composite that’s has both improved ductility and toughness. Coupled with the recent development in the field of additive manufacturing (AM) which provides huge benefits towards the drive for sustainable manufacturing. Thus this work examines the effectiveness of using selective laser melting (SLM) a type of AM process to fabricate AlSi10Mg specimens reinforced with carbon nanotubes (CNT). In addition, this work looks into using friction stir processing to post SLM process to overcome apparent defect known to be found in SLM fabricated parts. Parameter optimisation was first conducted by varying the laser power and scan speed to identify the optimal SLM parameters. Using laser power of 50W, 150W, 250W and 350W, scan speeds between 740mm/s and 1640mm/s. It was found the SLM was effective in fabricating AlSi10Mg-CNT specimens successfully using laser power of 150W and above. With optimal parameter of 350W and scan speed of 1040mm/s. Producing components with near full density and minimal defects. FSP was then conducted on three specimens with different selected parameters. AlSi10Mg with optimal parameters, AlSi10Mg-CNT with low energy density and AlSi10Mg-CNT with high energy density. FSP was found to provide significant grain refinement and improvement of ductility. Present defects in the SLM specimens were found to be significantly reduced after FSP. It was also noted that although both AlSi10Mg-CNT specimens showed increase in ductility, AlSi10Mg-CNT with low energy density resulted in higher ductility.